2020
DOI: 10.1080/23311932.2020.1806668
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and association analysis of Desi-type chickpea (Cicer arietinum L.) advanced lines under potential environment in North Gondar, Ethiopia

Abstract: The success of good breeding program usually depends upon the genetic variability present in the breeding materials, however, spatial and temporal studying on the amount, kind and magnitude of variability as well as genetic relationship of traits are not efficiently exploited yet. The present investigation was designed to assess the extent of variability, genetic advance, heritability and interrelation of different traits of 100 chickpea genotypes using triple lattice design in Takusa district, North Gondar, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
(21 reference statements)
9
13
0
Order By: Relevance
“…Moderate PCV and GCV were recorded for plant height, number of primary branches, number of secondary branches, number of pods per plant, Number of seeds per plant, biological yield, seed index, harvest index and seed yield per plant indicating that there is great scope for selection of this character (Table 3). Results were in accordance with the findings of Jeena et al [5], Thakur and Sirohi et al [6], Kishore et al [7], Tsehaye et al [8] and Shivashish et al [9] in chickpea.…”
Section: Resultssupporting
confidence: 92%
“…Moderate PCV and GCV were recorded for plant height, number of primary branches, number of secondary branches, number of pods per plant, Number of seeds per plant, biological yield, seed index, harvest index and seed yield per plant indicating that there is great scope for selection of this character (Table 3). Results were in accordance with the findings of Jeena et al [5], Thakur and Sirohi et al [6], Kishore et al [7], Tsehaye et al [8] and Shivashish et al [9] in chickpea.…”
Section: Resultssupporting
confidence: 92%
“…Genetic variation among individuals of a species is highly useful for breeders to identify and select the most desirable genotypes for the breeding programs (Bulti and Haji, 2019;Tsehaye et al, 2020). Estimation of genetic variation and its exploitation in hybridization programs is highly valuable for a successful crop breeding program (Rafiq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
Recently chickpea is being grown in more than 50 countries of the world (Tsehaye et al, 2020). Pakistan ranks 3 rd in chickpea producing countries but far below than world's average chickpea productivity per Abstract | Genetic variation occurring naturally in germplasm is highly valuable resource of alleles that can be deployed for genetic improvement of a species.
…”
mentioning
confidence: 99%
“…GCV and PCV estimations ranging from high to moderate (10.316, 10.942) reveal that there is a lot of variation across these traits, implying that there is extent for genetic improvement through effective selection. Thakur and Sirohi [15], Shweta and Yadav [16] and Tsehaye et al [17] all observed similar findings. The genotypic coefficient of variation estimations reflect the overall amount of genotypic variability present in the material.…”
Section: Resultsmentioning
confidence: 56%